Management of competencies in Algerian university libraries by adopting of ISO9001 standard : Central Library of Algiers2 Abou Al- Gasem saadallah as a model - ZIRAME , BAHIA; MEHADJBI , AISSA (Journal of Social Sciences and Humanities, 2021)
The adoption of competences management in university libraries has become imperative in our time due to the inefficient traditional systems and their inability to face various challenges especially modern technologies. In this context, through this scientific paper, we will address the reality of competences management in Algerian University Libraries and is there an application of the ISO 9001 standard relating to quality. We took the Central Library of the University of Algiers 2 as model, for that a set of approaches and comparisons were used, and the focus was on the indicators included in the standard related to the topic. And in order to test these indicators we projected them on the field of our study through the use of methodological tools such as observation and interview. In addition to the analysis of the latter, which we conducted with the director of the Central Library and the responsible for training at University Presidency level. Finally, we concluded that there is a partial application of the ISO 9001 standard in the Central Library of the University of Algiers 2.